Validitas Modul Ajar Berbasis Problem Based Learning Terintegrasi Google Sites pada Materi Ekosistem - Daud, Dwi Junievawati; Mamu, Hartono D.; Mustaqimah, Nur; Nusantari, Elya; Husain, Ilyas H. (Biocaster : Jurnal Kajian Biologi, 2025)
Biology learning in ecosystem materials still faces obstacles in the form of limited interactive learning tools, so that it has not been able to optimize students' problem-solving skills. The use of conventional devices that have not utilized digital technology makes the learning process less interesting and does not fully support independent learning. This study aims to describe the validity of google sites-integrated problem-based learning-based teaching modules on ecosystem materials. This type of research is Research and Development (R&D) with the ADDIE (Analyze, Design, Develop, Implement, and Evaluate) development model. The research subjects consisted of 31 students of class X. The instruments used included content and media validation sheets. The validation results showed that the teaching module was in the very valid category, with a percentage of 93% in the content aspect and 93.66% in the media aspect. Thus, google sites' integrated problem-based learning teaching module is suitable for use as a biology learning tool, because it is able to provide interactive, accessible learning, and support the improvement of students' problem-solving skills in a contextual and interesting manner.